IMPLICATIONS OF THE BASIC PRINCIPLES OF ISLAMIC ECONOMICS IN FORMING CHARACTERISTICS ECONOMIC INDEPENDENCE OF SINGLE MOTHERS - Rokamah, Ridho; Tri Cahyani, Yutisa; Nurohman, Dede; Sujianto, Agus Eko; Humaidi, Muchtim (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
This study aims to explore a solution between patriarchal interpretations and the reality of independent single mothers, as well as to break out of the confines of gender bias that limits the role of women. This study uses a qualitative approach by collecting primary data from six informants in Ponorogo, Ngawi, and Nganjuk Regencies as well as secondary data in the form of reports, books, and journals. Data analysis is carried out with internal and external criticism to ensure authenticity, as well as through classification, categorization, interpretation, and reflective-inductive analysis. The results showed that all informants had the characteristics of independence according to the theory of Spencer and Mustafa, such as initiative and creativity, problem-solving ability, perseverance, satisfaction, and freedom in choosing work. In addition, the characteristics of the informants were in line with the principles of Islamic economics, namely tawheed (oneness), equilibrium (justice and ihsan), free will (effort), and responsibility. The practical contribution of this study is to provide a reference for policy makers to support the role of single mothers through more inclusive policies. In addition, the results of this study can be a reference for the community in understanding that the independence of women, especially single mothers, is not a threat to social norms, but rather a positive contribution to economic development and family welfare.